Scanning the Muse - Aquino, Cesar Ruiz (Silliman Journal, 2022)
Retry springs from a sense of the beauty and terror in reation, personified as the Muse— whose presence is evoked in the poem. The presence can be identified with the sense. A bird's-eye-round-up of poetry through the ages will consistently confirm this – from the Song of Solomon to the work of Francisco Balagtas. Thus poetry can be considered religious, in a qualified sense of the word, in nature. It is essentially in praise, at times in dread, of the Muse or goddess, who is a metaphor or symbol for the creative force in creation. True poets, even when they have not been instructed in this esoterica, come to it by intuition or instinct.